Avaliação de desempenho e conforto térmico nos Módulos Antárticos Emergenciais - Martins, Wagner Gomes (2016)
The Emergency Antarctic Modules – MAE have been serving to the continuity of the activities undertaken at the Keller Peninsula in Antarctica since 2013, after the fire that destroyed the main part of the Comandante Ferraz Antarctic Station in 2012. Taking into account that MAE are located at a protected and extreme area, the aim of the presented work was to evaluate their performance, with an emphasis on the thermal comfort, considering the well-being of the users, the local climate conditions and the necessity of heating, which is carried out from the burning of fossil fuel. Following the procedures related to the Post- Occupancy Evaluation methodology, through the application of questionnaires and conducting temperature and humidity measurements, with the treatment of the collected data and analysis of results, problems concerning the air tightness, the distribution of the temperature in the rooms, and behavior in use were identified. Among the main results, it was found that there was no correlation between the external temperature and the internal one, being possible to infer that the envelope keeps the indoor thermal environment well isolated, despite the sealing problems, and/or that the heating system is capable of compensating the differences of temperature. It is possible that the observed temperature drifts have been caused by opening doors, especially in the summer period, when there are more users in the MAE. The results obtained by calculating the PMV, which represents the predicted mean vote of thermal sensation for a group of users in a building, along with the surveys, showed that the occurrence of cold thermal sensation gets worse with the use of garments with low coefficient of insulation. Making some adjustments in the building – for example, in the sealing, with an eventual substitution of material – it would probably be possible to achieve a high performance in the MAE and, in the same way, the comfort obtained would be even higher with some adjustments in the behavior in use – for example, using garments with greater isolation.